Pembelajaran Al-Qur’an di Taman Pendidikan al-Qur’an Roudlotul Tholabah Dusun Jemparing Desa Pakel - Abdul Halim; Achmad Zamroni; Wafiyul Ahdi; Mochammad Syafiuddin Shobirin (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Children should be taught to read the Qur'an as early as possible so that they feel like reading the Qur'an. So that it becomes the Qur'anic generation. Al-Qur'an Education Park (TPA/TPQ) is a non-formal institution of Islamic religious type that provides teaching on reading the Qur'an. Each TPQ must have a teacher who teaches it using different methods. The assistance provided at the Roudlotul Tholabah TPQ in the hamlet of Jemparing, Pakel village, was by jointly conducting a learning analysis using a SWOT analysis, then providing assistance for TPQ administrative arrangements as well as approaching the parents of children in the Jemparing area